METHODOLOGY FOR ASSESSING FUNCTIONAL LITERACY OF STUDENTS IN THE PROCESS OF TEACHING CHEMISTRY - Yusupova Nargiza Adashalievna (Bright Mind Publishing, 2025)
The article highlights the most important components of functional literacy, the quality of education, assessment of students' functional literacy at the international level, assessment of students' functional literacy and competence, assessment of students' functional literacy in the course of chemical education, assessment of the effectiveness of existing teaching methods, the concept of assessing students' functional literacy in the process of teaching chemistry, assessment methods, as well as approaches to the methodological component.
Keywords: Functional literacy.